The Value of the Indian Gazelle (Gazella gazella) : a Case Study in Haryana, India - Saxena, A. K.; Bisht, N. S.; Singh, C. J. (Indian Forester, 2008)
A study was undertaken in three villages of Bhiwani District in Haryana to assess the value of habitat function of planted forests. These villages were located at varying distance from a Blackbuck (Gazella gazella) Breeding Farm, which is a planted forest. Contingent valuation method was by asking the people to reveal their willingness to pay, both in terms of money as well as mandays, for the protection and improvement of the habitat for continued habitat function benefits. The total value of habitat functions provided by the farm was Rs. 15,71,641 per year for three villages out of which Rs. 12,24,112 per year came from the WTP in the form of labour mandays.